Pemberdayaan Keluarga dan Penguatan Peran Kader dalam Identifikasi Resiko Tinggi Maternal dan Neonatal sebagai Upaya Pencegahan Komplikasi di Desa Pucangrejo - Shinta Ika Sandhi; Desi Wijayanti Eko Dewi; Jumiatun; Pujiati Setyaningsih; Shinta Ayu Nani (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Community health cadres play a pivotal role as mediators between primary healthcare facilities and the community, particularly in strengthening preventive health programs. Continuous training is essential to enhance their competencies. Additionally, improving maternal health requires comprehensive education through dedicated maternal classes covering pregnancy management, childbirth, postpartum care, neonatal care, and screening for high-risk conditions. This community service program aimed to strengthen the capacity of health cadres and pregnant women in early detection of high-risk factors to prevent maternal and neonatal complications. Separate training sessions were conducted for 19 cadres and 10 pregnant women, using interactive lectures, participatory discussions, and hands-on practice. Pre- and post-training evaluations demonstrated significant improvement: the proportion of cadres with “good” knowledge increased from 63.2% to 84.2%, while pregnant women improved from 90% to 100%. These findings indicate that cadre training and maternal classes effectively enhance health literacy and strengthen the role of community health cadres at the village level.